Luminescence of samarium(iii) bis-dithiocarbamate frameworks: codoped lanthanide emitters that cover visible and near-infrared domains. Issue 26 (22nd June 2017) - Wang, Shanshan; Xu, Jin; Wang, Juan; Wang, Kai-Yao; Dang, Song; Song, Shuyan; Liu, Dan; Wang, Cheng
Abstract : A porous 3DSm-S-MOF with the white light emission, and especially for near-infrared (NIR) luminescent barcodes obtained from a single material has been explored. Abstract : Metal–organic frameworks constructed from lanthanides and organic linkers with oxygen or/and nitrogen donors (LnMOFs) are a very promising class of materials for various luminescence applications. However, the utilization of sulphur-donor ligands for sensitizing the luminescence of lanthanide ions is still hampered. Herein, a series of three-dimensional (3D) isostructural open frameworks: (H3 O)[Ln(pipzdtc)2 ]·1.5(H2 O)·2.5(CH3 NO) (Ln 3+ = Ce 3+, Nd 3+, Sm 3+, Eu 3+, Gd 3+, and Tb 3+, pipzdtc = piperazine-1, 4-dicarbodithiolate) (Ln-S-MOFs ) are synthesized. TheSm-S-MOF shows emission bands that range from the visible to the near-infrared (NIR) regions. The characteristic emission bands ofLn-S-MOFs (Ln = Ce 3+, Eu 3+, Gd 3+ and Tb 3+ ) cannot be observed. The isomorphousmixed-Sm-S-MOFs :Sm1− x Eu x -S-MOFs, Sm1− y Tb y -S-MOFs, Sm1− x − y Eu x Tb y -S-MOFs, andSm1− z Nd z -S-MOFs are synthesized via in situ doping. In the visible region, the color of the luminescence can be systematically modulated, and white light emission can be successfully achieved. Significantly, theSm1− z Nd z -S-MOFs show sharp NIR signals of both Sm 3+ and Nd 3+ centers. The NIR emission intensity ratios of Sm 3+ and Nd 3+ are almost linearly related to their atomic ratios. This work is a significant step forward towards versatile, easily prepared luminescentLn-S-MOFs suitable for practical applications including white light emission, and especially for NIR luminescent barcodes obtained from a single framework.